Introduction of Cut Nyak Dien's Figure in 2D Animation-Based Mobile Applications - Sabrina Az Zahrah; Syifa Hadiarti Aulia; Syifa Hanifa Wardani; Intan Permata Sari (Jurnal Pendidikan Multimedia (Edsence), 2023)
The introduction of National Indonesian heroes at this time is still a little using existing technology, where technology is currently developing rapidly. Making prototypes about Indonesian heroes is a form of appreciating, remembering and remembering the existing heroes. Thus, the design of the "Leaftory" Cut Nyak Dien application is expected to make target users with the target of elementary school children ages 7-12 years able to know and remember Indonesian heroes by utilizing online mobile-based technology. The design of this application also pays attention to UI/UX by presenting an attractive appearance in the form of text, graphics and 2D animation to positively impact users. Developers also make trials to target users so that there is feedback from developers to users and vice versa.